PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBIASAAN SHALAT BERJAMA’AH SISWA SD NEGERI WIDODAREN 4 KABUPATEN NGAWI - Bermi, Wibawati (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2021)
The role of Islamic religious education is recognized by those who use educational services with unsatisfactory results. Therefore, the author can say that the current learning system still needs to be seriously studied to create a more effective and useful way of learning. Therefore, Islamic religious education can produce quality students with scientific knowledge of noble character and sincere charity. The results obtained, the description is: (1) The implementation of Islamic Religious Education at SDN Widodaren 4 Ngawi Regency has been going well and in accordance with the established curriculum (2) The habit of praying in congregation for students is quite good, but there are still many things that need to be done. improved by setting an example, fostering, guiding and helping to give understanding. (3) The role of Islamic Religious Education teachers in the habit of praying in congregation for students at SDN 4 Widodaren, Ngawi Regency as role models, giving advice, as well as providing motivation and direct guidance to students who are not enthusiastic enough to influence the habit of praying in congregation. Keywords: Role, Habituation, Congregational Prayer